Biomarkers Enhance Discrimination and Prognosis of Type 2 Myocardial Infarction. Issue 16 (20th October 2020) - Horiuchi, Yu; Wettersten, Nicholas; Patel, Mitul P.; Mueller, Christian; Neath, Sean-Xavier; Christenson, Robert H.; Morgenthaler, Nils G.; McCord, James; Nowak, Richard M.; Vilke, Gary M.; Daniels, Lori B.; Hollander, Judd E.; et al.
Abstract : Background: The observed incidence of type 2 myocardial infarction (T2MI) is expected to increase with the implementation of increasingly sensitive cTn assays. However, it remains to be determined how to diagnose, risk-stratify, and treat patients with T2MI. We aimed to discriminate and risk-stratify T2MI using biomarkers. Methods: Patients presenting to the emergency department with chest pain, enrolled in the CHOPIN study (Copeptin Helps in the early detection Of Patients with acute myocardial INfarction), were retrospectively analyzed. Two cardiologists adjudicated type 1 MI (T1MI) and T2MI. The prognostic ability of several biomarkers alone or in combination to discriminate T2MI from T1MI was investigated using receiver operating characteristic curve analysis. The biomarkers analyzed were cTnI, copeptin, MR-proANP (midregional proatrial natriuretic peptide), CT-proET1 (C-terminal proendothelin-1), MR-proADM (midregional proadrenomedullin), and procalcitonin. The prognostic utility of these biomarkers for all-cause mortality and major adverse cardiovascular event (a composite of acute myocardial infarction, unstable angina pectoris, reinfarction, heart failure, and stroke) at 180-day follow-up was also investigated. Results: Among the 2071 patients, T1MI and T2MI were adjudicated in 94 and 176 patients, respectively. Patients with T1MI had higher levels of baseline cTnI, whereas those with T2MI had higher baseline levels of MR-proANP, CT-proET1, MR-proADM, and procalcitonin. The area under the receiver operating characteristic curve for the diagnosis of T2MI was higher for CT-proET1, MR-proADM, and MR-proANP (0.765, 0.750, and 0.733, respectively) than for cTnI (0.631). Combining all biomarkers resulted in a similar accuracy to a model using clinical variables and cTnI (0.854 versus 0.884, P =0.294). Addition of biomarkers to the clinical model yielded the highest area under the receiver operating characteristic curve (0.917). Other biomarkers, but not cTnI, were associated with mortality and major adverse cardiovascular event at 180 days among all patients, with no interaction between the diagnosis of T1MI or T2MI. Conclusions: Assessment of biomarkers reflecting pathophysiologic processes occurring with T2MI might help differentiate it from T1MI. All biomarkers measured, except cTnI, were significant predictors of prognosis, regardless of the type of myocardial infarction. Abstract : Supplemental Digital Content is available in the text.